Comparing the Effect of Albumin 5% versus Ringer Lactate on Blood Coagulation in Trauma-Induced Coagulopathy during Initial Resuscitation - Yahya Abdel Tawab Mohammed Meky* (SVU - International Journal of Medical Sciences)
Background: Trauma-induced coagulopathy (TIC) denotes abnormal blood clotting that occurs as a result of a physical injury. During the initial stages of trauma-induced coagulopathy development, there is usually a condition of reduced blood clotting ability, leading to bleeding. Objectives: This study aimed to ascertain the difference between using albumin and ringer lactate in resuscitation of traumatized patients and their impact on blood coagulation. Patients and methods: This prospective comparative study was carried out on 80 patients aged above 18 years old, both sexes, trauma induced coagulopathy clinical score over 10. Patients were divided into two equal groups: Group A: received ringer lactate, and group B: received albumin. Results: Coagulation test at day 1, 2 and 3 of initial resuscitation were insignificantly different between both groups. Regarding coagulation tests in Group A, B were insignificantly different amongst coagulation tests at days 1 and 3 of initial resuscitation. However, there was improvement of the coagulation test results during day 3 of initial resuscitation. Changes in platelet count and hemoglobin at different intervals of time were insignificantly different between both groups. Conclusion: The effect of administration of albumin solution with Ringer’s lactate on blood coagulation in TIC during initial resuscitation showed no difference as regard effect on coagulation profile between two groups, but patients received albumin showed better improvement in resuscitation parameters on the second day in comparison to the patients received Ringer’s lactate.